Avaliação dos efeitos promovidos pela sibutramina, associada ou não à nicotina, nos tecidos reprodutivos de ratas albinas - Camargo, Isabel Cristina Cherici [UNESP]; Gonçalves, Juliana Grizante Segantin [UNESP] (My University, 2013)
Sibutramine is a drug recommended clinically for the treatment of obesity, but there are women that use the drug for maintenance of body weight. Many time this use occur associate to habit of tabagism, being the nicotine the main toxic compound in the cigarette. The goal of study was to evaluate the side effects promoted by sibutramine, associated or not to nicotine, in the reproductive tissue of adult female rats. Wistar animals (n =30), were distributed in the groups: a) Control A (0.3 mL of distilled water; oral); b) Sibutramine (15 mg/kg of body weight; oral); c) Control B (0.3 mL of saline solution; intraperitoneal); d) Nicotine (4.0 mg/kg of body weight; intraperitoneal); e) sibutramine + nicotine. The treatments were conducted during 30 consecutive days (single dose, daily). Sibutramine, associated or not to nicotine, affected the folliculogenesis and luteogenesis. There were significant alterations (p<0.05) in the thickness of uterine layers, considerate each treatment. In conclusion, the administration isolated of sibutramine or nicotine promoted deleterious effects in the reproductive tissues of female rats and these effects were potential in the group that received both drugs.
Assessment of the effects promoted by sibutramine, associated or not to nicotine, in reproductive tissues of albino female rats
Keywords: Histomorphometry; Nicotine; Ovaries; Rats; Sibutramine; Uterus